The identification of Germany’s horizontal and vertical industrial clusters: A new approach and first empirical results - Titze, Mirko; Brachert, Matthias; Kubis, Alexander (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
If regional development agencies assume the cluster concept to be an adequate framework to promote regional growth and competitiveness, it is necessary to identify industrial clusters in a comprehensive manner. Previous studies used a diversity of methods starting with specific regional case studies, input-output methods and different concentration measures. This article presents a new instrument in empirical cluster research — the Qualitative Input-Output Analysis-, which offers the possibility to identify industrial cluster in conjunction with concentration measures. Especially, this method allows the combination of an identified critical mass of regional firms with the necessity of interaction of these firms within an input-output framework. Applying this method to Germany’s “Arbeitsmarktregionen” we find that 103 “Arbeitsmarkregionen” show first signs of horizontal industrial clusters, while only 28 regions are able to attract vertical industrial clusters. 139 “Arbeitsmarkt-regionen” did not show signs of industrial clusters according to the research design.